The Effect of Cigarette and Water Pipe Smoking on Some of Blood Parameter - K. Abbas, Amal; Fouad Ali, Layla (Iraqi Journal of Science, 2023)
Current study aimed to investigate the effect of cigarette and water pipe smoking on smoker immunity comparing to non smoker. Twenty blood samples were collected from smoker students and twenty blood samples from non smoker students from Baghdad university in 2014.The results showed that there was increase in W.B.Cs total count in smoker group comparing to non smoker in a significant differences P<0.05. The differential W.B.Cs count results shows that there are increase was neutrophiles and Monocytes while there is decrease in lymphocytes in smoker group comparing to non smokers in a significant differences P<0.05 .Also the results revealed that there is an increase in percentage of phagocytosis to Staphyllociccus aureus bacteria by phagocytic cells in smoker group comparing to non smoker group.